Concepções teóricas e práticas da psicologia social comunitária nos cursos de psicologia nas instituições de ensino superior no nordeste brasileiro - Santos, Adriana Pereira dos (2017)
This research consists of an investigation of the theoretical and practical conceptions of Community Social Psychology (PSC) in the Psychology courses of Higher Education Institutions (IES) in the Northeast of Brazil, from a look at the theories and practices related to the formation of Psychologist and the consolidation of Psychology in the psi fields where community practices are necessary. It begins with the understanding that Community Social Psychology presents itself as an alternative to social change, having been one of the currents that make up the critical movement of Psychology in Brazil. Theoretical and practical conceptions inserted in the pedagogical context, mainly in what concerns the formation and intervention in Community Social Psychology, was problematized in the sense of raising elements that contribute to an analysis of the panorama of Community Social Psychology as a discipline taught in the IES of the Northeast of Brazil. The specific objectives were based on the identification of the IES in the Northeast of Brazil that offer the undergraduate course in Psychology and the analysis of the bibliographic reference and reference related to the discipline of PSC and / or similar. The methodology is qualitative, through analysis of the programs of the PSC and / or similar subjects of 131 IESs in the Brazilian Northeast that offer the undergraduate course in Psychology. The data generated were analyzed from the Content Analysis (Bardin, 2006). At the end, it was verified that the PSC as a discipline was consolidated in the Brazilian Northeast with its own identity, although fragility was verified regarding the dimension of the emphases and stages that are offered, suggesting the importance of being reviewed by IESs , In the sense that changes are necessary to act according to the guiding principles of the PSC that can only occur if the academic and professional spaces become a process of critical reflection and production of new knowledge allied to the practice.